WSCUC Substantive Change Screening Form: Master of Arts in Psychology
The mission of the graduate program in Psychology at California State University Channel Islands is to provide qualified students the opportunity to earn a master's degree in Psychology. The program's objective is to prepare students for doctoral study in Psychology or research-based careers. The program emphasizes the development of the quantitative and critical thinking skills that allow for analytical approaches to better understand societal and theoretical issues.Student training will emphasize breadth of knowledge in psychological theories and principles, along with advanced quantitative and qualitative methodologies for application to research questions and real world problems. The program's strengths include the opportunity to work closely with faculty on a thesis project or with community partners on an internship. Intensive training in statistical analysis is another hallmark of the program. These opportunities will ensure that students graduate with the skills needed to transition successfully to their careers or a doctoral program. The program meets institutional learning objectives by training graduate students who have knowledge of theories that can help explain issues affecting human society, as well as the analytical skills to support data-driven understanding of these issues. Students will also gain experience with effective communication of complex issues and how to address problems. The program develops independent research skills through participation in an internship-based experience or through a thesis. As such, the program supports all aspects of the mission of California State University Channel Islands.